Investigation of Chemical Looping Materials: Iron-Manganese Oxide System - Anilkumar, Aparna (My University, 2011)
It is widely known that increasing levels of greenhouse gases in the atmosphere absorb heat radiation and so raise the earth’s surface temperature. CO2 forms 77% of global anthropogenic emissions; so stabilizing CO2 levels could provide a means to control the human impact on global average temperatures. Fossil fuel combustion, being a major source of CO2 emission would be a good place to begin. Two relatively new techniques for CO2 capture are Chemical Looping Combustion (CLC) and Chemical Looping with Oxygen Uncoupling (CLOU). Both methods use two fluidized bed reactors, an air reactor and a fuel reactor with oxygen carriers (usually metal oxides) circulating between them. In CLC, the oxygen carriers react with fuel and in CLOU, they release gaseous O2 for fuel conversion. Once depleted of O2, they move on to the air reactor to be replenished. As seen, oxygen carriers are an integral part of these processes. To improve their performance, it is possible to combine and form a bi-metal oxide system. One such system that shows promise, especially in CLOU, is the iron manganese oxide. It is produced, usually by freeze granulation of Fe2O3 and Mn3O4 in specific proportions. This thesis studies three samples in particular: M24F1100, M40F1100 and M79F1100 containing 24, 40 and 79 wt% Mn3O4 respectively. The oxides were studied while heating them in inert and oxidising atmospheres. X-ray diffraction of the samples was conducted once they cooled down. The data collected is expected to provide an insight into the behaviour of the system. The results show that M24F1100 showed the most stable O2 uncoupling but had the least capacity to transport O2. M79F1100 had the highest capacity but did not react with O2 until cooled to 780oC. XRD results show similar phase behaviour in M24F1100 and M40F1100. This leads to the idea that M40F1100 could show stable O2 uncoupling as well, perhaps at a lower temperature.
Keywords: Kemi; Chemical Sciences